Predicting fragment intensities and retention time of iTRAQ‐ and TMTPro‐labeled peptides with Prosit‐TMT. Issue 19 (24th May 2022) - Gabriel, Wassim; Giurcoiu, Victor; Lautenbacher, Ludwig; Wilhelm, Mathias
Abstract: Isobaric labeling increases the throughput of proteomics by enabling the parallel identification and quantification of peptides and proteins. Over the past decades, a variety of isobaric tags have been developed allowing the multiplexed analysis of up to 18 samples. However, experiments utilizing such tags often exhibit reduced identification rates and thus show decreased analytical depth. Re‐scoring has been shown to rescue otherwise missed identifications but was not yet systematically applied on isobarically labeled data. Because iTRAQ 4/8‐plex and the recently released TMTpro 16/18‐plex share similar characteristics with TMT 6/10/11‐plex, we hypothesized that Prosit‐TMT, trained exclusively on 6/10/11‐plex labeled peptides, may be applicable to these isobaric labeling strategies as well. To investigate this, we re‐analyzed nine publicly available datasets covering iTRAQ and TMTpro labeling for samples with human and mouse origin. We highlight that Prosit‐TMT shows remarkably good performance when comparing experimentally acquired and predicted fragmentation spectra (R of 0.84 ‐ 0.9) and retention times (ΔRT95% of 3% ‐ 10% gradient time) of peptides. Furthermore, re‐scoring substantially increases the number of confidently identified spectra, peptides, and proteins.